(untitled) (Texas Journal of Engineering and Technology, 2022)
The article assesses the results of the activities of the textile and clothing and knitwear industry of Uzbekistan for 2017-2020. The role of the industry in the development of the economy and industry, the growth of exports, the introduction of a cluster development model, and the provision of employment are shown. Development priorities are shown.